Implementasi Metode RAD Pada Sistem Jasa Pengiriman Ekspedisi PT. Bina Karya Majujaya - Nuris, Nuzuliarini; Sutiyono, Dirgantara Nowan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Data recording system on expedition services at PT. Bina Karya Majujaya still done manually and written by administrative staff which can cause a long process of data collection of goods to be sent. Therefore the work system becomes inaccurate, unorganized and messy. This can be an obstacle in the search for sending data to be processed or currently being processed. Therefore the author intends to design an expedition information system at PT. Bina Karya Majujaya. Design and build an expedition service information system at PT. Bina Karya Majujaya which is a solution to simplify recording and reporting by applying the research method development of the RAD method and development applications in the form of delivery order websites in web programming language with MySQL database media.With the Expedition Service Information System at PT. Bina Karya Majujaya is expected to simplify the process of data management, files as well as reporting.